Village funds and access to finance in rural Thailand - Lukas Menkhoff; Ornsiri Rungruxsirivorn (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
This paper examines whether recently introduced village funds, one of the largest microfinance programs ever implemented, improve access to finance. Village funds are analyzed in a cross-sectional approach in relation to competing financial institutions. We find, first, that they reach the target group of lower income households better than formal financial institutions. Second, village funds provide loans to those kinds of borrowers which tend to be customers of informal financial institutions. Third, village funds help to reduce credit constraints. Thus, village funds provide services in the intended direction. However, they do this to a quite limited degree, questioning their efficiency.
Keywords: O16; O17; G21; 330; informal financial institutions; microfinance; credit constraint; Thailand; Asia; Ländlicher Finanzmarkt; Mikrofinanzierung; Informeller Finanzsektor; Agrarkredit; Verschuldungsrestriktion; Armutspolitik; Thailand